NLRP3 Regulated CXCL12 Expression in Acute Neutrophilic Lung Injury - Peng Y; Wu Q; Tang H; Chen J; Wu Q; Yuan X; Xiong S; Ye Y; Lv H (Dove Medical Press, 2020)
Yanwen Peng,1 Qiongli Wu,2 Hao Tang,3 Jingrou Chen,1 Qili Wu,1 Xiaofeng Yuan,4 Shiqiu Xiong,5 Yujin Ye,6 Haijin Lv7 1The Biotherapy Center, The Third Affiliated Hospital, Sun Yat-sen University, Guangzhou 510630, People’s Republic of China; 2Department of Immunology, Zhongshan School of Medicine, Sun Yat-sen University, Guangzhou 510080, People’s Republic of China; 3Department of General Practice, The First Affiliated Hospital, Sun Yat-sen University, Guangzhou 510080, People’s Republic of China; 4The General Intensive Care Unit, The Third Affiliated Hospital, Sun Yat-sen University, Guangzhou 510630, People’s Republic of China; 5Cell Biology Group, National Measurement Lab, LGC Fordham, Cambridgeshire CB7 5WW, UK; 6Department of Rheumatology, The First Affiliated Hospital, Sun Yat-sen University, Guangzhou 510080, People’s Republic of China; 7The Surgical and Transplant Intensive Care Unit, The Third Affiliated Hospital, Sun Yat-sen University, Guangzhou 510630, People’s Republic of ChinaCorrespondence: Haijin Lv; Yanwen Peng Email lvhaijin@mail.sysu.edu.cn; pengyw@mail.sysu.edu.cnBackground and Purpose: Both NLRP3 inflammasome and chemokines are involved in the initiation and development of acute lung inflammation, but the underlying mechanism is still elusive. The present study investigated the role of chemokines and NLRP3 in recruiting neutrophils in the early phase of acute lung injury.Methods: In an endotoxin (lipopolysaccharide [LPS])-induced acute lung injury model, we measured the lung injury severity, myeloperoxidase (MPO) activity and chemokine profiles in wild-type (WT) and NLRP3 knockout (NLRP3–/–) mice, and then identified the key chemokines by specific antibody blockage.Results: The results showed that NLRP3 deficiency was associated with alleviating lung damage, by reducing alveolar epithelial cell apoptosis and decreasing neutrophil accumulation. Furthermore, compared with WT mice, IL-1β, CCL2, CXCL1, CXCL5 and CXCL12 levels from the serum of NLRP3–/– mice were much lower after exposure to LPS. However, in lung tissue, only lower CXCL12 levels were observed from the NLRP3–/– ALI mice, and higher levels of CXCR4 were expressed in NLRP3–/– neutrophils. Blockage of CXCL12 dramatically relieved the severity of ALI and reduced neutrophil accumulation in the lung.Conclusion: NLRP3 alters CXCL12 expression in acute lung injury. CXCL12 is crucial for neutrophil recruitment in NLRP3-mediated neutrophilic lung injury.Keywords: NLRP3, acute lung injury, ALI, neutrophils, chemokines, CXCL12